In vivo trafficking of a tumor-targeting IgE antibody: molecular imaging demonstrates rapid hepatobiliary clearance compared to IgG counterpart. (1st January 2021) - Man, Francis; Koers, Alexander; Karagiannis, Panagiotis; Josephs, Debra H.; Bax, Heather J.; Gilbert, Amy E.; Dodev, Tihomir S.; Mele, Silvia; Chiaruttini, Giulia; Crescioli, Silvia; Chauhan, Jitesh; Blower, Julia E.; et al.
ABSTRACT: IgE antibodies elicit powerful immune responses, recruiting effector cells to tumors more efficiently and with greater cytotoxicity than IgG antibodies. Consequently, IgE antibodies are a promising alternative to conventional IgG-based therapies in oncology (AllergoOncology). As the pharmacokinetics of IgE antibodies are less well understood, we used molecular imaging in mice to compare the distribution and elimination of IgE and IgG antibodies targeting the human tumor-associated antigen chondroitin sulfate proteoglycan 4 (CSPG4). Anti-CSPG4 IgE and IgG1 antibodies with human Fc domains were radiolabeled with 111 In. CSPG4-expressing A375 human melanoma xenografts implanted in NOD- scid IL2rg -/- mice were also engrafted with human immune cells by intravenous administration. 111 In-anti-CSPG4 antibodies were administered intravenously. Their distribution was determined by single-photon emission computed tomography (SPECT) and ex vivo gamma-counting over 120 h. SPECT imaging was conducted from 0 to 60 min after antibody administration to precisely measure the early phase of IgE distribution. 111 In-labeled anti-CSPG4 IgG and IgE showed serum stability in vitro of >92% after 5 days. In A375 xenograft-bearing mice, anti-CSPG4 IgE showed much faster blood clearance and higher accumulation in the liver compared to anti-CSPG4 IgG. However, tumor-to-blood and tumor-to-muscle ratios were similar between the antibody isotypes and higher compared with a non-tumor-targeting isotype control IgE. IgE excretion was much faster than IgG. In non-tumor-bearing animals, early SPECT imaging revealed a blood clearance half-life of 10 min for IgE. Using image-based quantification, we demonstrated that the blood clearance of IgE is much faster than that of IgG while the two isotypes showed comparable tumor-to-blood ratios.